Plicacora, a new genus of Thyrididae from Mozambique and Zambia (Lepidoptera: Thyrididae: Siculodinae: Siculodini) - Elliott, Imogen R. (Zootaxa, 2025)
A monotypic genus Plicacora gen. nov. is erected to include one new species P. maputoana sp. nov. following the discovery of several unusual specimens from Mozambique and Zambia in the collections of the African Natural History Research Trust (ANHRT). The new genus and species are compared to the allied Cecidothyris Aurivillius, 1910 from which it differs in phenotype and genital morphology. The generic placement of C. longicorpa Whalley, 1971 is considered in reference to Plicacora gen. nov. and the biogeography of the new species, known from a unique coastal environment, is briefly discussed.